Comparison of complication rates and incidences associated with different peripherally inserted central catheters (PICC) in patients with hematological malignancies: a retrospective cohort study. Issue 1 (2nd January 2020) - Scrivens, Nicholas; Sabri, Elham; Bredeson, Christopher; McDiarmid, Sheryl
Abstract: Patients with hematological malignancies (HM) or undergoing hematopoietic cell transplantation (HCT) require reliable vascular access. Peripherally inserted central catheters (PICC) meet this need, however, studies suggest these patients have higher rates of PICC-associated complications. This retrospective cohort study evaluates the influence of PICC type on the rates and incidences of complications. Four hundred and eighty-five dual lumen PICCs were inserted into 469 complex patients with HM or undergoing HCT: 161 Groshong ®, 60 PowerPICC ® Solo, 165 BioFlo ®, and 99 Arrow ® . The rates and incidences of complications differed significantly across the PICC types. The overall rate of complication ranged from 7.40 to 26.4/1000 catheter days (CDs). The rate of deep vein thrombosis (0.31–1.48/1000 CDs) and occlusion differed across the PICC types, while the rate of central line-associated bloodstream infection (0.53–0.74/1000 CDs) did not. Following multivariate adjustment, PICC type was associated with complication rate. This highlights that PICC type should be considered in clinical decisions.